Unveiling Social Realities through Language: A Comparative Analysis of Halliday, van Dijk, and Fairclough’s Frameworks in Social Research: English - Selviana Napitupulu; Partohap Saut Raja Sihombing; Immanuel Onasis Kha Napitupulu (Yayasan Bayt Shufiya Nusantara, 2026)
Discourse Analysis (DA) has emerged as a critical instrument in social sciences to uncover power dynamics and social realities, particularly within the context of Sustainable Development Goals (SDGs). However, researchers often encounter methodological ambiguity when selecting the most appropriate framework among diverse linguistic traditions. This study conducts a critical comparative analysis of three dominant paradigms: M.A.K. Halliday’s Systemic Functional Linguistics, Teun A. van Dijk’s Socio-Cognitive Approach, and Norman Fairclough’s Critical Discourse Analysis (as discussed in O'Regan, 2021). Using a qualitative library research method, this study deconstructs the epistemological foundations and analytical tools of each approach. The findings indicate that Halliday’s framework offers a microscopic lens on textual texture and register, van Dijk’s approach bridges text and society through cognitive mental models, while Fairclough’s model examines the dialectical relationship between language and institutional power. The study concludes with a comparative matrix, providing a methodological roadmap for researchers to align these frameworks with specific social inquiries, such as education, inequality, or policy analysis.